Innovative Approaches in the Management of Educational Facilities: Synergizing Digital Inventory and Preventive Maintenance - Makmun, Sukron; Marif, Hairul (Educative: Jurnal Ilmiah Pendidikan, 2025)
The management of educational facilities and infrastructure is a fundamental component in improving the quality of learning. However, many schools still face significant challenges, including inaccurate asset inventories, inadequate maintenance systems, and limited human resources and budgets. This article aims to analyze strategies for inventory and maintenance of educational facilities through a literature review approach. The study examines approximately 30 scholarly sources, including accredited journals, educational management books, and relevant national regulations. The findings indicate that effective management strategies include the implementation of digital-based inventory systems, systematic asset classification, preventive maintenance, and collaboration between internal administrative teams and external technical staff. On the other hand, challenges such as limited technical competence and funding constraints can be addressed through adaptive school leadership, capacity-building training for human resources, and active participation from all school stakeholders. The implications of this study emphasize the importance of integrating technological innovation and managerial approaches in developing a sustainable, accountable, and digitally responsive system for managing educational facilities. Thus, this study provides strategic contributions not only to the theoretical development of educational management but also to its practical implementation at the institutional level.